Sosialisasi Keuangan Akuntansi Syariah Pada Anggota IKM Gula Aren Di Kecamatan Rambah Kabupaten Rokan Hulu Provinsi Riau - Rona Naula Oktaviani; Rosyetti Rosyetti; Lintang Nur Agia; Poppy Camenia Jamil; Annisa Lifriance (Asosiasi Dosen Akuntansi Indonesia, 2020)
This implementation of community service activities (PKM) is carried out for the members of the IKM HPR Palm Sugar farmer in Kaiti Village in Rambah District, Rokan Hulu distict, Riau Province. This activity is a service aimed at fostering farmer groups in terms of making financial reports. The limited knowledge of farmers in preparing financial reports especially in sharia accounting has made farmers unable to calculate with certainty the price of palm sugar. The purpose of this activity is to aims knowledge and understanding for the member so they can apply Islamic accounting financial reporting that correctly accordance with Islamic principles. But in reality, IKM members only record in the form of daily notes (in the form of receipt of basic raw materials, cash income and disbursements, accounts receivable and payable). His dedication method is socialization, material presentation, and discussion with IKM members. The conclusion is that HPR IKM members are still lacking in recording and management in their business, especially sharia accounting financial reports. So this PKM was held to provide socialization on the importance of recording financial statements in running a business, so that the financial management of IKM members can be carried out correctly and according to Islamic sharia in the Islamic accounting financial statements. Keywords: Islamic Accounting Financial Statements, Small and Medium Industries (IKM).